Quantitative Evaluation of Patient Positioning Error Using CBCT 3D Gamma Density Analysis in Radiotherapy - Lee, Soon Sung; Min, Chul Kee; Cho, Gyu Suk; Han, Soorim; Kim, Kum Bae; Jung, Haijo; Choi, Sang Hyoun (Progress in Medical Physics, 2017)
Radiotherapy patients should maintain their treatment position as patient setup is very important for accurate treatment. In this study, we evaluated patient setup error quantitatively according to Cone-Beam Computed Tomography (CBCT) Gamma Density Analysis using Mobius CBCT. The adjusted setup error to the QUASAR™ phantom was moved artificially in the superior and lateral direction, and then we acquired the CBCT image according to the phantom setup error. To analyze the treatment setup error quantitatively, we compared values suggested in the CBCT system with the Mobius CBCT. This allowed us to evaluate the setup error using CBCT Gamma Density Analysis by comparing the planning CT with the CBCT. In addition, we acquired the 3D-gamma density passing rate according to the gamma density criteria and phantom setup error. When the movement was adjusted to only the phantom body or 3 cm diameter target inserted in the phantom, the CBCT system had a difference of approximately 1 mm, while Mobius CBCT had a difference of under 0.5 mm compared to the real setup error. When the phantom body and target moved 20 mm in the Mobius CBCT, there are 17.9 mm and 13.5 mm differences in the lateral and superior directions, respectively. The CBCT gamma density passing rate was reduced according to the increase in setup error, and the gamma density criteria of 0.1 g/cc/3 mm has 10% lower passing rate than the other density criteria. Mobius CBCT had a 2 mm setup error compared with the actual setup error. However, the difference was greater than 10 mm when the phantom body moved 20 mm with the target. Therefore, we should pay close attention when the patient’s anatomy changes. KCI Citation Count: 0